SYNTACTICAL ANALYSIS ON SENTENCE PATTERNS IN THE SELECTED SONG LYRICS OF TAYLOR SWIFT’S ALBUM LOVER - Rizkiyah, Muthiatur; Arifin, M. Bahri; Pratiwi Sudirman, Eka (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
ABSTRACTThis study presents the syntactical analysis on sentence patterns in the selected songs of Taylor Swift’s Album Lover by using the theory of sentence patterns by Quirk and Greenbaum. This research also uses the theory of tree diagram by Bornstein to help the researcher in analyzing sentence patterns. In this study the researcher used descriptive method and content analysis approach. The data of this research are words, phrases, and sentences related to the analysis of sentence pattern especially in _You Need to Calm Down_, _Cruel Summer_, _Death by Thousand Cut_, _Paper Rings_, and _Daylight_ song. From the results, through the sentences chosen by the researcher, the researcher found that the largest number of the sentence pattern in Taylor Swift’s song lyrics is in pattern 3: S + Vt + dO which is used for 5 times. Finally, there are three patterns which are not used at all, which are pattern 1: S + LV + A, pattern 6: S + Vt + iO + dO, and pattern 7: S + Vi. Those patterns were not used because the researcher did not find any data or lyrics in Taylor Swift’s selected songs and selected sentences in Lover album that use any of those patterns.*Keywords:* Syntactic Analysis, Sentence Pattern, Tree Diagram, Lover’s AlbumABSTRAKPenelitian ini menyajikan analisis sintaksis pada pola kalimat di lagu-lagu pilihan Taylor Swift pada album Lover dengan menggunakan teori pola kalimat dari Quirk dan Greenbaum. Penelitian ini juga menggunakan teori diagram pohon dari Bornstein untuk membantu peneliti dalam menganalisis pola kalimat. Dalam penelitian ini peneliti menggunakan metode deskriptif dan pendekatan analisis isi. Data penelitian ini berupa kata, frasa, dan kalimat yang berkaitan dengan analisis pola kalimat terutama pada lagu _You Need to Calm Down_, _Cruel Summer_, _Death by Thousand Cut_, _Paper Rings_, dan _Daylight_. Dari hasil penelitian, melalui kalimat-kalimat yang dipilih oleh peneliti, peneliti menemukan bahwa jumlah pola kalimat terbesar dalam lirik lagu Taylor Swift adalah pola 3: S + Vt + dO yang digunakan sebanyak 5 kali. Terakhir, ada tiga pola yang tidak digunakan sama sekali, yaitu pola 1: S + LV + A, pola 6: S + Vt + iO + dO, dan pola 7: S + Vi. Pola-pola tersebut tidak digunakan karena peneliti tidak menemukan data atau lirik pada lagu-lagu pilihan Taylor Swift dan kalimat-kalimat pilihan dalam album Lover yang menggunakan pola-pola tersebut.*Kata Kunci:* Analisis Sintaksis, Pola Kalimat, Diagram Pohon, Album Lover